An electrochemical sensor based on a modified glassy carbon electrode for detection of epinephrine in the presence of theophylline - Hadi Beitollahi; Zahra Sarbandian (ADMET and DMPK, 2024)
Background and purpose: Neurotransmitters are chemical messengers that enhance and balance signals between cells and target cells in the body. They are vital to the body's ability to function. Epinephrine is one of the most essential catecholamine neurotransmitters with an important biological and pharmacological role in the mammalian central nervous system. Therefore, it is very important to develop sensitive, simple, and fast methods for the determination of this compound. Experimental approach: In the present work, a glassy carbon electrode (GCE) modified with the cerium oxide-zinc oxide (CeO2-ZnO) nanocomposite (CeO2-ZnO/GCE) was developed for the sensitive and quick detection of epinephrine. The CeO2-ZnO nanocomposite was prepared by hydrothermal method. Electrochemical methods such as voltammetry and chronoamperometry techniques were used to investigate the performance of the developed sensor. Key results: The resulting CeO2-ZnO/GCE showed a remarkable response towards the determination of epinephrine. The electrochemical sensor demonstrated a wide dynamic linear range from 0.1 to 900.0 μM for analysis of epinephrine. The LOD equalled 0.03 μM for epinephrine. In addition, the electrochemical sensor had good feasibility for concurrent detection of epinephrine and theophylline. Furthermore, experimental outputs indicated that the oxidation peaks of epinephrine and theophylline were separated by a 685 mV difference between the two peaks in PBS at a pH of 7.0. Also, an electrochemical sensor has been employed to analyse epinephrine in real samples (urine and epinephrine Injection). Conclusion: The good and acceptable analytical performance of the developed sensor can provide a promising tool for the analysis of epinephrine in real samples.